2017
DOI: 10.1080/10503307.2017.1365183
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in adult anxious and avoidant attachment during cognitive behavioral therapy for panic disorder

Abstract: Overall, avoidant and anxious attachment improved during CBT for PDA. This change was related to and preceded by improved anxiety sensitivity, avoidance behaviors, and emotion regulation. These findings suggest that CBT for panic probably has downstream effects on attachment representations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 66 publications
3
25
0
Order By: Relevance
“…Notably, the cognitive intervention related to anxiety sensitivity, which is described in the first stage of the model, implies that therapist's physical presence is not essential. In contrast, the interventions regarding avoidance behaviors highlight the central role of the therapist: "external or internalized therapist encourages independent exploration of experiences" (Stage 2) and: "CBT: Therapist encourages exploration of experiences of bodily sensations without suppression or avoidance" (Stage 3; Zalaznik et al, 2019). These both refer to the presence of the therapist.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the cognitive intervention related to anxiety sensitivity, which is described in the first stage of the model, implies that therapist's physical presence is not essential. In contrast, the interventions regarding avoidance behaviors highlight the central role of the therapist: "external or internalized therapist encourages independent exploration of experiences" (Stage 2) and: "CBT: Therapist encourages exploration of experiences of bodily sensations without suppression or avoidance" (Stage 3; Zalaznik et al, 2019). These both refer to the presence of the therapist.…”
Section: Discussionmentioning
confidence: 99%
“…However, we should not assume that this type of psychotherapy is appropriate for all Shidu parents with PTSD. In China, there are many more severe cases of post-traumatic stress disorder among Shidu parents, and they cannot get over the grief of losing their only child, lose hope for life, and refuse all help [8]. It is difficult for researchers to intervene in the Shidu parents with such strong resistance to psychotherapy.…”
Section: Limitations and Prospects Of Cognitive-behavioral Erapy In T...mentioning
confidence: 99%
“…Alliance has also been shown to mediate the relationship between client attachment and psychotherapy outcome (subjective distress, interpersonal relations, and social role performance) in clients presenting with mixed pathology (e.g., mood and anxiety disorders; Byrd et al, 2010). One study in PD patients showed that changes in anxious attachment preceded improvement in alliance across CBT (Zalaznik et al, 2019).…”
Section: Clinical Impact Statementmentioning
confidence: 99%
“…An insecure AS appears to be a predisposition for the development of anxiety disorders (AD) as well as a maintaining factor (Colonnesi et al, 2011; Esbjorn et al, 2012; Levy et al, 2011; Manning et al, 2016) and vice versa (Davila et al, 1997; Horesh et al, 2014). The constant sense of threat in AD probably leads to frequent activation of the attachment system (Zalaznik et al, 2019). Earlier studies show that AD patients often have an insecure and mainly preoccupied/anxious AS (de Ruiter & Van Ijzendoorn, 1992; Manning et al, 2016; Marazziti et al, 2007; Nielsen et al, 2017).…”
mentioning
confidence: 99%